A successful method of transplanting adult Ecklonia radiata kelp, and relevance to other habitat‐forming macroalgae. Issue 5 (6th July 2021) - Layton, Cayne; Cameron, Matthew J.; Shelamoff, Victor; Tatsumi, Masayuki; Wright, Jeffrey T.; Johnson, Craig R.
Abstract : The ability to successfully transplant adult kelp has applications not only for ecological experiments, but also for habitat conservation and restoration projects. However, approaches to the long‐term transplanting of adult kelp (especially for stalked or 'stipitate' species), and the communication of these methods, has been relatively haphazard, often due to poor results and excessive mortality. Here, we provide a brief communication to describe a method to effectively transplant the stipitate kelp Ecklonia radiata —the most widespread and abundant kelp in Australasia—and which allowed the transplanting of >1, 000 adult kelp over 1.5 ha. We also discuss additional observations relevant to the success of transplanting kelp (such as donor age/size), and the applicability of this method to other habitat‐forming macroalgae. Our method involved securing the adult Ecklonia to the substratum using large bands made from recycled rubber, which held the holdfast firmly but gently against the substratum. Re‐attachment of the adult kelp typically occurred within 3–6 weeks, while rates of survivorship were approximately 75% and not affected by the density nor size of the transplanted patch. This method could also readily be adapted to suit different substratum types and other species of kelp and habitat‐forming algae. Ultimately, this transplanting method adds to the collection of effective techniques for restoring habitat‐forming macroalgae, especially for stipitate species where few methods have been communicated.